Personal Workspace in an Architectural Design Studio as an Efficient Behavior Setting - Masoomeh Ahmadi; Maryam Farhady (آموزش مهندسی ایران, 2017)
Built environments are formed through definition of public and private territories and organization of spatial hierarchies. Appropriate definition of space increases people's sense of belonging to their environment. Educational environments, including architectural schools, also need the above territories. This study introduces the personal workspace, as a supplement to the public workspace in a design studio, as an effective factor on the quality of the environment for architectural education. In this regard, this study aims to introduce the personal workspace as an efficient behavior setting in the architectural design studio. The descriptive analysis in this research is achieved through library studies on theoretical background, observations and interviews on 12selected architecture schools in 10 countries. The necessity of personal workspace in design studios is discussed from two approaches: architectural education and behavioral sciences. The selected cases are analyzed according to the formation of personal workspace as a behavior setting. The results reveal that the personal workspace is configured according to the students' real needs. Also, it has a positive effect on their learning quality and increasing the sense of belonging to the educational environment. However, based on educational policies and spatial potentials, the personal workspace forms a territory with a range from physical to psychological boundaries. Finally, defining personal workspace with clear boundaries, while also considering its flexibility and connection to the public workspace, would better determine the efficiency of the personal workspace in the design studio.